The Utilization of the OJAD Website to Improve Japanese Speaking Skills in Vocational High School - Yuliani, Siti; Hernawati, Heni (Universitas Pendidikan Indonesia (Indonesia University of Education), 2024)
Japanese differs from Indonesian in letters, grammatical patterns, pronunciation, and vocabulary. These differences make students difficult to understand Japanese because some vocabularies are similar in pronunciation. For example, the word ichi which means one similar to the word shichi which means seven. Moreover, many students mispronounced long sound as short such as the word ohayou (good morning) which is pronounced as ohayo. Students also find it difficult to pause when pronouncing sentences in Japanese which produces unnatural accents. To overcome these problems, this study aims to use the OJAD (Online Japanese Accent Dictionary) website for learning Japanese, particularly to improve students’ speaking skills. OJAD is a website in which there are various features and one of the features is the Suzuki-kun Prosody Tutorial. Through this feature, students will be able to practice pronouncing words or sentences in Japanese according to pronunciation accuracy, including accents and intonations. This research employs a descriptive qualitative study, with participants from grade X students of a Vocational High School in Cilacap, Central Java. The results showed that after using the OJAD website, students’ Japanese speaking skills improved, and able to pronounce Japanese with better pronunciation and intonation. In addition, learning Japanese using the OJAD website as a media lesson makes students more enthusiastic and enjoy learning Japanese. The results of this study are expected to be a reference for improving proficiency in Japanese, especially in terms of Japanese speaking skills.